Endocrine Effects of Valproate in Adolescent Girls with Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The effects of epilepsy and/or valproate (VPA) monotherapy on physical growth, weight gain, pubertal development, and hormonal status of 68 consecutive female patients aged 6-20 years (20 premenarche, 60 postmenarche) were studied at the Institute for Endocrinology and Diabetes, Schneider Children's Medical Center, and Tel Aviv University, Israel.